Implementasi Projek Penguatan Profil Pelajar Pancasila Profil Pelajar Rahmatan Lil Alamin di MtsN 6 Agam - Suci Endrizal; Ulva Rahmi; Nurhayati Nurhayati (Pusat Riset dan Inovasi Nasional, 2023)
The quality of Indonesian education is currently very worrying. Changing times have a big impact on the direction of education, the curriculum is expected to be able to respond to these changes so that students can learn in accordance with the direction of changes that occur. The Pancasila student profile is the embodiment of Indonesian students as lifelong learners who have global competence who behave in accordance with Pancasila values. . Of course, to achieve this, students throughout Indonesia need to work together to achieve international quality students with local cultural values. This research uses a descriptive method with the aim of combining information related to the research subject and the behavior of the research subject in a certain era. It is hoped that this activity will give birth to commendable morals in students. By understanding what is read during prayer, it will create solemnity and enjoyment in worship which will radiate praiseworthy qualities in students. Some students are quick to remember and learn things, but on the other hand there are some students who have difficulty understanding and memorizing.